GAMBARAN TATALAKSANA PASIEN PREEKLAMPSIA YANG TERKONFIRMASI COVID-19 DAN NON-COVID-19 DI RSUD ULIN BANJARMASIN - Nor Hayatun Thaibah; Ferry Armanza; Siti Wasilah; Hariadi Yuseran; Lena Rosida (Homeostasis, 2022)
Preeclampsia is hypertension in pregnancy which is characterized with blood pressure of 140/90 mmHg after 20 weeks of gestation, accompanied by proteinuria.3. There are three types of drugs that are often used in preeclampsia treatment, they are nifedipine, methyldopa, and MgSO4. This study was aimed to find out the description of confirmed covid-19 and non covid-19 preeclampsia patients treatment at Ulin Hospital, Banjarmasin in the COVID-19 period seen from administration of MgSO4, antihypertensive, method and time of termination. This study applied descriptive method with data collection through medical records. The sampling technique used purposive sampling which was selected based on the criteria. In this study, a sample of 176 preeclampsia patients with confirmed COVID-19 and non-COVID-19 were obtained. However, from the 176 samples, which met the criteria, only 55 preeclampsia patients had confirmed COVID-19 and 80 non-COVID-19 preeclampsia patients. The results showed that all severe preeclampsia patients with confirmed COVID-19 were given MgSO4 with a percentage of 100%.. Antihypertensives were often given was a combination of methyldopa + nifedipine. The most common method of delivery was by cesarean section.